2015
DOI: 10.1093/nar/gkv1483
|View full text |Cite
|
Sign up to set email alerts
|

OxyR-dependent formation of DNA methylation patterns in OpvABOFFand OpvABONcell lineages ofSalmonella enterica

Abstract: Phase variation of the Salmonella enterica opvAB operon generates a bacterial lineage with standard lipopolysaccharide structure (OpvABOFF) and a lineage with shorter O-antigen chains (OpvABON). Regulation of OpvAB lineage formation is transcriptional, and is controlled by the LysR-type factor OxyR and by DNA adenine methylation. The opvAB regulatory region contains four sites for OxyR binding (OBSA-D), and four methylatable GATC motifs (GATC1–4). OpvABOFF and OpvABON cell lineages display opposite DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 60 publications
5
52
0
Order By: Relevance
“…We also observed an increase (136% ± 6%) in activity of P 169* - lacZ relative to P 169 - lacZ in WT , while the activity of P 2901* - lacZ was decreased compared to P 2901 - lacZ . The mutations may alter the target sequence for other regulator(s) in addition to the methylation properties, thereby affecting transcription directly or indirectly in a positive or negative fashion [42, 43]. For example, P 2901 is bound by the master cell cycle regulator CtrA in vivo and the Δ mucR1/2 mutation is known to affect CtrA expression [17], whereas the P 169 promoter is affected by the phosphate starvation response (see below) [44, 45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed an increase (136% ± 6%) in activity of P 169* - lacZ relative to P 169 - lacZ in WT , while the activity of P 2901* - lacZ was decreased compared to P 2901 - lacZ . The mutations may alter the target sequence for other regulator(s) in addition to the methylation properties, thereby affecting transcription directly or indirectly in a positive or negative fashion [42, 43]. For example, P 2901 is bound by the master cell cycle regulator CtrA in vivo and the Δ mucR1/2 mutation is known to affect CtrA expression [17], whereas the P 169 promoter is affected by the phosphate starvation response (see below) [44, 45].…”
Section: Resultsmentioning
confidence: 99%
“…In bacteria local methylation changes may correlate with altered virulence behaviour and may underlie cell cycle-control in pathogens, endosymbionts or other microbial systems. Methylation is known to influence virulence functions in γ-proteobacteria, often by imposing bistability from phase-variable virulence promoters in subpopulations via transcriptional regulators such as Lrp, Fur or OxyR [5, 9, 42, 48, 5155]. Phenotypic heterogeneity in antibiotic drug tolerance in vivo (a state known as persistence), which is acquired in a low fraction of bacterial cells, may also underlie epigenetic changes induced stochastically by methylation, either deterministically (during the cell cycle) or environmentally.…”
Section: Discussionmentioning
confidence: 99%
“…A differential expression of several genes encoding virulence factors such as pap, agn43, sci1 in E.coli (Blyn et al, 1990 ; Henderson and Owen, 1999 ; Brunet et al, 2011 ), but also gtr , or opvAB in Salmonella (Broadbent et al, 2010 ; Cota et al, 2016 ), is related to a differential methylation state of the GATC sites found in their respective promoters. This is caused mostly by differences in DNA affinity, depending on the DNA methylation state, of various transcriptional repressors (OxyR, Lrp, or Fur).…”
Section: Discussionmentioning
confidence: 99%
“…When DNA methylation regulates gene expression, heterogeneous methylation creates multiple phenotypes within isogenic populations ( Casadesús and Low, 2013 ). This phenotypic plasticity aids rapid adaptation to changing environmental pressures ( Cota et al, 2016 ) and nutrient constraints ( Atack et al, 2018 ) for other bacteria. However, no study has examined heterogeneous methylation in M. tuberculosis .…”
Section: Introductionmentioning
confidence: 99%